Оцінка генофонду люцерни та його використання в селекції за умов підвищеної кислотності ґрунтів - Бугайов, В.Д.; Горенський, В.М.; Мамалига, В.С. (Фактори експериментальної еволюції організмів, 2016)
Aim. Research and estimation of gene pool of alfalfa on basic economic-valuable signs for its further using of selection for the terms of an increase acidity of soil. Methods. Field (realization of phonological supervisions and accounts, crossbreed analysis), laboratory (account of the seed productivity), mathematically-statistical (objective estimation of the obtained experimental data). Results. On results research of present gene pool of alfalfa (collection standards 92 pc.), hybrid populations (F₂, 42) and plant-breeding numbers (34 pc.) the distinguished genotypes. Tolerant to acidity of soil from relatively by a high feed and seminal yield, that exceeded a standard sort Syniukha on these indexes on 6–23% – 6–33% accordingly. Conclusions. The informative database of new feedstock is taken by valuable signs for the further selection of alfalfa. A new created variety Radoslawа alfalfa crop, tolerant to conditions of increased acidity of the soil (ph 5.2–5.3).